Subtle Differences in Symbiont Cell Surface Glycan Profiles Do Not Explain Species-Specific Colonization Rates in a Model Cnidarian-Algal Symbiosis - Parkinson, John E.; Tivey, Trevor R.; Mandelare, Paige E.; Adpressa, Donovon A.; Loesgen, Sandra; Weis, Virginia M. (Frontiers in Microbiology, 2018)
Mutualisms between cnidarian hosts and dinoflagellate endosymbionts are foundational to coral reef ecosystems. These symbioses are often re-established every generation with high specificity, but gaps remain in our understanding of the cellular mechanisms that control symbiont recognition and uptake dynamics. Here, we tested whether differences in glycan profiles among different symbiont species account for the different rates at which they initially colonize aposymbiotic polyps of the model sea anemone Aiptasia (Exaiptasia pallida). First, we used a lectin array to characterize the glycan profiles of colonizing Symbiodinium minutum (ITS2 type B1) and non-colonizing S. pilosum (ITS2 type A2), finding subtle differences in the binding of lectins EEL and UDA that distinguish between high-mannoside and hybrid-type protein linked glycans. Next, we enzymatically cleaved glycans from the surfaces of S. minutum cultures and followed their recovery using flow cytometry, establishing a 48-72 hour glycan turnover rate for this species. Finally, we exposed aposymbiotic host polyps to cultured S. minutum cells masked by EEL or UDA lectins for 48 hours, then measured cell densities the following day. We found no effect of glycan masking on symbiont density, providing further support to the hypothesis that glycan-lectin interactions are more important for post-phagocytic persistence of specific symbionts than they are for initial uptake. We also identified several methodological and biological factors that may limit the utility of studying glycan masking in the Aiptasia system.